Testing for variation in technical efficiency of hospitals in Ireland - Gannon, Brenda (Economic & Social Studies, 2005)
Funding in Irish hospitals is partially based on case mix, whereby resources are redistributed annually to hospitals with greater efficiency. Accurate measurement of efficiency is essential, so in this paper, we use Data Envelopment Analysis and Stochastic Frontier Analysis to measure technical efficiency of acute public hospitals in Ireland between 1995 and 2000. The results provide estimates of average technical efficiency in the hospital sector in Ireland for the first time, and highlight the variation in technical efficiency levels across hospitals. Internationally, the results contribute to the growing literature on the comparison of DEA and SFA methodologies.
Keywords: Technical efficiency; Hospitals; Ireland; Hospital funding